RANCANGAN SYSTEM REWARDS TERHADAP KEPUASAN KERJA DALAM MEMBANGUN LOYALITAS KARYAWAN DI REVOLT INDUSTRY - Ellyana Ellyana; Sujoko Efferin (CALYPTRA, 2018)
Everyone has different interests and needs, as well as employees. These differences shape employee' expectations, motivations, and character. Management control system required by the company in controlling employee behavior because this control system acts as a tool to overcome the problem, one of them is by providing incentive system. Not only the incentives employees receive by doing a job, but the intrinsic rewards that employees feel during the work can also be said to build employee loyalty to the company itself. Implementation of incentive system greatly affects employee performance, if employees are satisfied with the incentives they receive then employees will be loyal and show better performance. Conversely, if employee expectations in work didn’t meet with company’s policy then employee behavior will lead to intention turnover. Along with the development of human resources, the problem of turnover intention is a distinctive challenge for companies nowadays since the turnover intention is an unpredictable event. Uncontrolled employee behavior will lead to intention turnover.